Whole‐genome profiling and shotgun sequencing delivers an anchored, gene‐decorated, physical map assembly of bread wheat chromosome 6A. (19th June 2014) - Poursarebani, Naser; Nussbaumer, Thomas; Šimková, Hana; Šafář, Jan; Witsenboer, Hanneke; van Oeveren, Jan; Doležel, Jaroslav; Mayer, Klaus F.X.; Stein, Nils; Schnurbusch, Thorsten
Summary Bread wheat (Triticum aestivum L.) is the most important staple food crop for 35% of the world's population. International efforts are underway to facilitate an increase in wheat production, of which the International Wheat Genome Sequencing Consortium (IWGSC) plays an important role. As part of this effort, we have developed a sequence‐based physical map of wheat chromosome 6A using whole‐genome profiling (WGP™). The bacterial artificial chromosome (BAC) contig assembly tools fingerprinted contig (fpc) and linear topological contig (ltc) were used and their contig assemblies were compared. A detailed investigation of the contigs structure revealed that ltc created a highly robust assembly compared with those formed by fpc. The ltc assemblies contained 1217 contigs for the short arm and 1113 contigs for the long arm, with an L50 of 1 Mb. To facilitate in silico anchoring, WGP™ tags underlying BAC contigs were extended by wheat and wheat progenitor genome sequence information. Sequence data were used for in silico anchoring against genetic markers with known sequences, of which almost 79% of the physical map could be anchored. Moreover, the assigned sequence information led to the 'decoration' of the respective physical map with 3359 anchored genes. Thus, this robust and genetically anchored physical map will serve as a framework for the sequencing of wheat chromosome 6A, and is of immediate use for map‐based isolation of agronomically important genes/quantitative trait loci located on this chromosome.